Survey Paper on Internet Thing of Smart Cities - Patel, Jeetendra; Patel, Rakesh; Singh, Prateek Kumar (International Journal For Research In Advanced Computer Science And Engineering, 2016)
As this world we can assume that ,what could be the meaning of “smart” so ,it’s have lots of meaning like ,knowledgeable, a smarty, which can be perfect in all field. In general term we can define smart city as smartness of city. Internet content of infinity of things many of them are useful and many of they were of no use generally i.e. internet are designed to support smart city, by solving the problem of communication system of every technologies used by citizens and by city’s requirement .This paper present the internet things of make smart cities, we know smart cities I things “smart” means intelligent cities, sustainable cities, digital cities and so on. The concept of “smart cities” is response to this challenge. This paper explores smart cities as nvironment of open and userdriven innovation for experimenting and validating Future internet enabled services and future internet experimentally driven research and projects in the domain of living labs that the smart cities project developed in urban area a performed in collaboration with the cities municipality.